Evaluation of mass drug administration programme for elimination of lymphatic filariasis in Bidar district, Karnataka - Hoolageri, Mahesh S.; Kamath, Ramachandra; Ravikumar, K.; G., Jagadish; Kamath, Surekha (International Journal Of Community Medicine And Public Health, 2018)
Background: Lymphatic filariasis (LF) is endemic in 83 countries and territories, with more than a billion people at risk of infection. Filariasis has been a major public health problem in India next only to malaria. Study was done to assess coverage and compliance of mass drug administration (MDA) against lymphatic filariasis in Bidar district. Methods: This cross-sectional coverage evaluation survey was done in one urban and three rural clusters in district. The data was compiled, tabulated and analyzed using proportions. Results: A total of 739 subjects were interviewed, male subjects constituted about 57.5%. 96.58% persons have received the drugs. Out of the 678 persons who have received the drugs, 85.4% persons have consumed the drugs. Only 31.95% of study subjects consumed tablets in front of health workers. A total of 99 subjects not consumed tablets, 22.22% told drug distributor did not visit, 21.21% were out of station and 14.14% subjects were not aware. 24 persons suffered from nausea and vomiting. Conclusions: There is an urgent need for more effective drug delivery strategies and also proper IEC should be done to educate and to improve the coverage and compliance in the districts.